Hakikat Asas Pemisahan Horizontal Dalam Hukum Adat - Adwin Tista (Al-Adl : Jurnal Hukum, 2022)
The principle of horizontal separation in Indonesian Agrarian Law has a philosophical meaning of maximizing the utility of land for people's lives, including for the indigenous communities. The existence of this is to realize social justice for the people of Indonesia. The tangible manifestation of the horizontal separation is in the case of plantation business management between land owners in cooperation with plantation business actors as capital owners. However, in practice, there needs to be an adjustment from the application of the horizontal separation principle with the rules of customary law that apply to indigenous peoples so as not to cause problems or conflicts of norms, because that's why the horizontal separation principle in customary law must essentially be based on the value of utility and justice. The solution to this problem is to carry out legal reconstruction in the field of land administration to support the principle of horizontal separation which will be a solution to maximize the function of the land. In the context of realizing equitable social justice, both from land owners and capital owners by making a government regulates plant registration in the context of plantations and building registration, in addition to the existing Government Regulation No. 24/1997 on Land Registration. This research uses a normative method by conducting a literature study using two legal materials, namely primary legal materials and secondary legal materials, with a legal approach, a conceptual approach, and a case approach.